Karamunting screening as an antifungal using the In Silico method targeting N-myristoyltransferase - Samsul Hadi; Kunti Nastiti (Institute of Computer Science (IOCS), 2023)
Karamunting has been empirically used by the community in overcoming itching disorders due to fungi. Therefore the purpose of this study was to screen in silico the content of Karamunting against N-myristoyltranseferase protein. The method used in this study was In Silico screening using PLANTS docking and the materials used were thirteen compounds contained in Karamunting. The results of this study are docking scores from -123.628 to -77.3801 and residues that have similarities with native ligands when interacting with N-myristoyltransferase, namely one to three amino acids, the predicted value using PASSonline ranges from 0.101 to 0.583. The conclusion of this study was obtained three compounds that have the potential as antifungals with the N-myristoyltransferase inhibitor mechanism, these compounds are α-tocopherol-quinone; α-tocopherol A; blumeatin.